Research on the lifetime of the switch and assumptions of increasing it - Gailienė, Inesa; Podagėlis, Igoris; Slepakovas, Olegas (Transport, 2008)
The switch is the most complicated and expensive component of a superstructure of the railway track. It requires particular attention and maintenance. The lifetime of the switch depends on its operating conditions and on a lifetime of its separate components, mostly the tongue and the frog. Defects of these two components emerge considerably earlier than that of the others. Reliable, uninterrupted and safe railway traffic depends on condition of the switch components. Condition of the switch components depends on their maintenance and determination and elimination of the defects in time. A very important task is to assure qualitative, long‐lasting and cost‐efficient switch appliance. In order to realize these objectives it is necessary: to improve the switch construction; to use materials that should have improved physical and mechanical characteristics for the manufacture of the switch; to improve organization and performance of the switch maintenance and repair applying modern techniques and methods. In order to determine dependence of load amount on tongue, frog and stock rail wear, analysis of technical and running conditions of replaced switches in the stations of Lithuanian railway lines in 2002, 2003 and 2005, is presented in the article. Authors’ purpose is: to determine wear reasons of switch components; to examine load amount dependence on tongue, frog and stock rail wear and to submit the suggestions on improving the switch construction, installation and maintenance in order to increase the lifetime of the switch.First published online: 27 Oct 2010